Impact of internal aqueous phase gelation on in vitro lipid digestion of epigallocatechin gallate‐loaded W1/O/W2 double emulsions incorporated in alginate hydrogel beads. Issue 10 (14th September 2022) - Wang, Wenjuan; Dong, Zhe; Gu, Liyuan; Wu, Bi; Ji, Suping; Xia, Qiang
Abstract : Abstract: Our objective was to investigate if the internal aqueous phase gelation of Water‐in‐oil‐in‐water double emulsions encapsulated in alginate beads would affect their structural stability and lipid hydrolysis during in vitro digestion. Therefore, bioactive molecules such as (−)‐epigallocatechin gallate were encapsulated into different types of delivery systems: original double emulsions (as control) and incorporated double emulsions (filled in alginate hydrogel beads), both with non‐gelled or gelled internal aqueous phase by locust bean gum and κ‐carrageenan. After 2 h of gastric digestion, the gelled original emulsions showed smaller mean droplet diameters and less coalescence during the in vitro simulated gastrointestinal digestion compared to the non‐gelled original emulsions. For the incorporated emulsions, oil droplets released from beads aggregated under intestinal conditions, and the rate of lipolysis was delayed. Interestingly, the internal aqueous phase gelation also impacted the rate and cumulative amount of free fatty acids (FFA) released. Practical Application: The combination of incorporating (−)‐epigallocatechin gallate‐loaded double emulsions into the alginate hydrogel matrix and gelling the internal aqueous phase was a benefit to regulating the rate and extent of lipid digestion for specific applications in foods, such as to control blood lipid levels and appetite.